Managing the risk of intimacy: accounts of disclosure and responsiveness among people with HIV and intimate partners of people with HIV. Issue 10 (3rd October 2018) - Green, Helena D.; Weeks, Margaret R.; Berman, Marcie; Mosher, Heather I.; Abbott, Maryann; Garcia, Natalie
Abstract: It is well known that concerns about sexual risk tend to decline among people in intimate relationships where there is established commitment and trust. In the context of relationships at increased risk for HIV transmission, interactions involving disclosure and partner responsiveness are key to maintaining intimacy and physical safety. This paper explores concepts of risk and sexual intimacy articulated by a community sample of 30 people living with HIV and their intimate relationship partners. Data revealed the shifts in intimate relationship dynamics upon the disclosure of an HIV diagnosis, the importance of intimacy in the context of managing one or both partners' HIV care and responses to new advances in HIV prophylaxis. Findings suggest that participants' experiences of self-disclosure and partner responsiveness most often resulted in an increased sense of protectiveness from and for partners. This suggests that health-promoting messaging should be adapted to be more relevant to intimate couple communication and mutual support.